Internalization of Ethics and Morals to Generate Quality and Integrity Elections in 2024 - Mulawarman; Djamaluddin, Sudirman; Tusriadi; Amalia, Dea Rizky; Hidayatullah, Fauzan (Global Writing Academica Researching & Publishing, 2025)
This study aims to find out what steps must be taken to produce elections with quality and integrity in 2024. The research method used is a type of qualitative research with a descriptive analysis approach. Data was obtained through primary and secondary data and analyzed in depth. Based on the data obtained through literacy studies and interviews, in producing quality and integrity elections, it is not only the organizers who internalize ethics and morals, but three important elements in it, namely: the community as voters with integrity, election organizers with integrity, and election participants who integrity. Through the ethical and moral internalization of these three elements, the hope that all parties desire is the presence of a quality leader by creating a healthy, democratic political environment through the 2024 election results.